PSMC5 Promotes Proliferation and Metastasis of Colorectal Cancer by Activating Epithelial–Mesenchymal Transition Signaling and Modulating Immune Infiltrating Cells - He, Zirui; Yang, Xiao; Huang, Ling; Zhou, Leqi; Zhang, Sen; Sun, Jing; Zheng, Minhua; Ma, Junjun; Feng, Bo; Zang, Lu (Frontiers in Cell and Developmental Biology, 2021)
We designed the present study to access the roles and mechanisms of PSMC5 in colorectal cancer (CRC). Transcriptomic and clinical data from public datasets and our center were retrospectively analyzed. Functional assays were performed to investigate the effects of PSMC5 on CRC cells. The results showed that PSMC5 was significantly higher in cancer than normal tissues. Moreover, patients with higher expression of PSMC5 showed poorer prognosis. Silencing of PSMC5 dramatically suppressed the proliferation and invasion of CRC cells, while overexpression led to the opposite. In addition, we screened downstream targets and found that PSMC5 regulates multiple pathways including epithelial–mesenchymal transition, hypoxia, and immune response. Consistently, we found that PSMC5 was negatively correlated with levels of CD8 + T cells and B cells while promoting infiltration of macrophages and neutrophils. Collectively, these findings suggested that PSMC5 was a promising biomarker and target for immune therapy for CRC.